The Concept of Business Ethics in Islamic Perspective - Maman Wahyudi (STKIP Taman Siswa Bima, 2024)
Ethics is the foundation of human civilization that permeates all aspects of our lives, influencing behavior, decisions, and interactions. In the context of business, business ethics encompass the application of moral principles in all business activities, such as management, marketing, finance, and operations. Business ethics help identify and address complex moral dilemmas in the global business world. Islamic business ethics, rooted in the moral principles of the Quran and Sunnah, emphasize justice, honesty, trust, and social responsibility. It prohibits practices such as riba, gharar, and maysir, and encourages business practices like mudharabah, musharakah, and murabahah that are in accordance with Sharia principles. By applying Islamic business ethics, companies can build harmonious relationships with all stakeholders while making a positive contribution to society and the environment.